The total protein band profile of the green leafhoppers (Nephotettix virescens) and the leaves of rice (Oryza sativa) infected by tungro virus - ANI SULISTYARSI; SURANTO SURANTO; SUPRIYADI SUPRIYADI (Nusantara Bioscience, 2012)
Abstract. Sulistyarsi A, Suranto, Supriyadi. 2012. The total protein band pattern of the green leafhoppers (Nephotettix virescens) and the leaves of rice (Oryza sativa) infected by tungro virus. Nusantara Bioscience 4: 32-35. Tungro virus is one of most important diseases of rice plants caused by double infection with RTBV and RTSV which is transmitted by Nephotettix virescens Distant. The interaction between host and virus-vector are still quitted difficult to understand. The aims of this study were: (i) to know the character of the total protein band pattern of rice plants infected with tungro virus compared to the health one, (ii) to look at the different between the band profiles of total protein of N. virescens that consume the host rice plants infected by tungro virus and that of the healthy rice plants. Total protein band profiles of rice plants were identified using SDS-PAGE. To extract the leaves, buffer mercapto-ethanol was used, while the sample extraction of green leafhoppers employed buffer PBS IX, and for staining the protein coomassie brilliant blue was used. Data were analyzed descriptively based on the score of the migration of the band (Rf). The results showed that the protein contains every 0.5 g of healthy leaves and the infected by the virus were 0.567 g and 1.011 g respectively. Clear difference of the protein pattern was found in the healthy plant and the infected one. In general, the entire band in the infected plant was much thicker compared to the infected leaves. Protein bands with a higher quantity were expressed by the protein on the molecular weight of 108 and 117 kDa. These proteins are presumably from the group of ?-galactosidase and bovine serum albumin. The function of such proteins is still unknown, but it may be related to the plant’s responses to virus infection, because the protein did not appear in the healthy plants. The total protein content of both N. virescens which acquired the healthy leaves and the infected one were 0.1395 g and 0.1546 g respectively. Qualitatively, there was no significant difference in the protein expression in those vectors, but slightly thicker band were observed in the infected leaves.